2017
DOI: 10.5194/acp-2017-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric pollution concentrations over the Eastern Mediterranean during summer – A review

Abstract: <p><strong>Abstract.</strong> The Eastern Mediterranean (EM) is one of the regions in the world where elevated concentrations of primary and secondary gaseous air pollutants have been reported frequently, mainly in summer. This review discusses published studies of the atmospheric dispersion and transport conditions characterizing this region during the summer, followed by a description of some essential studies dealing with the corresponding concentrations of air poll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
(199 reference statements)
0
3
0
Order By: Relevance
“…The winter (December-February) and fall (September-November) months have a lower seasonal mean AOD, while during the summer we see a concentration of somewhat higher values around the western coast of the Dead Sea, where the northwestern wind penetrates the Negev, bringing humidity and air masses from the densely-populated industrial coast of central Israel as well as from Europe (Derimian et al, 2006). Previous studies has found that during this season and at this location, fine particle loadings with anthropogenic origin are dominant (Derimian et al, 2006;Dayan et al, 2017).…”
Section: Aod Patternmentioning
confidence: 50%
See 1 more Smart Citation
“…The winter (December-February) and fall (September-November) months have a lower seasonal mean AOD, while during the summer we see a concentration of somewhat higher values around the western coast of the Dead Sea, where the northwestern wind penetrates the Negev, bringing humidity and air masses from the densely-populated industrial coast of central Israel as well as from Europe (Derimian et al, 2006). Previous studies has found that during this season and at this location, fine particle loadings with anthropogenic origin are dominant (Derimian et al, 2006;Dayan et al, 2017).…”
Section: Aod Patternmentioning
confidence: 50%
“…During the summer season, the persistent Persian Trough system cause local stability beneath the seasonal strong inversion layer at about 1 km above mean-sea-level. This allows the Mediterranean sea breeze to influence the area greatly alongside its unique topography, by enhancing the impact of local emission sources (Kishcha et al, 2016;Alpert et al, 1997;and Dayan et al, 2017) and transporting dust and anthropogenic aerosols from afar (Derimian et al, 2006;Derimian et al 2017). Specifically, Derimian et al (2017) have shown that chemical composition, microphysical and optical properties of atmospheric aerosol deep inland in the Negev Desert of Israel were found to be influenced by daily occurrences of sea breeze flow from the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies in this area revealed higher particle-phase PBDEs levels in summer than in winter (Besis et al 2015;Besis et al 2016;Cetin and Odabasi 2008;Gevao et al 2013). The reduced mixed layer and the weak west winds, characterizing the summer in Eastern Mediterranean, lead to reduced ventilation rates, preventing an effective dilution of the contaminants (Dayan et al 2017). The present study presents the G/P partitioning of PBDEs, their mass size distribution, and explores the long-range transport potential during an intensive 2week summertime sampling campaign concurrently carried out at four quasi-background sites around the Aegean Sea.…”
Section: Introductionmentioning
confidence: 79%